Lucy Mvubelo's role in the South African Trade Unions, 1960-1974 (2) - Strydom, Irene; Coetzer, Pieter (Faculty of Humanities, University of the Free State, 2012)
Lucy Mvubelo’s career as one of the foremost black feminist trade union leaders stretched from 1942 to 1987. In a first article on her role in the trade unions the authors stressed the importance of her leadership qualities and her remarkable potential in establishing the SA Congress of Trade Unions (SACTU) and Federation of Free African Trade Unions (FOFATUSA). During these later years of her career she remained instrumental in the development of the South African trade unions. She still worked in close cooperation with Anna Scheepers and Johanna Cornelius. Labour legislation of the apartheid government, however, hampered their work. Mvubelo nevertheless fought for the dignity of all workers. Till 1987 Mvubelo, Scheepers and Cornelius ensured that legislation was changed to give all workers the opportunity for better housing, education and equal pay for equal work. Bread-and-butter issues were of utmost importance in Mvubelo’s struggle for a better dispensation for all workers. When she retired in 1987 she was regarded as instrumental in bringing about phenomenal changes in the black trade union movement. In this second article the authors focus on her role in the SA trade unions between 1960 and 1974.
Keywords: SACTU; FOFATUSA; SA trade unions; Lucy Mvubelo; Anna Scheepers; Johanna Cornelius; Labour relations; Equal union rights